Traditional games as a tool for improving psychosocial development: a comparative study of structured and progressive learning models - Julianti, Rekha Ratri; Suherman, Adang; Ma'mun, Amung; Budiana, Dian; Sari, Eka Fitri Novita (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2025)
Background: Pressure in the school environment, academic demands, and high social expectations often increase the vulnerability of children and adolescents to psychosocial problems. Bad interactions, such as bullying or social isolation, can contribute to their mental state and hinder their social engagement. Research Objectives: The aim is to determine the difference in the influence of a deliberately structured psychosocial learning model and a deliberately structured progressive learning model through traditional games on psychosocial development. Methods: This research used a quasi-experimental design with a pre-test-post-only control group design with a model of more than one experimental group and sample selection using a purposive sampling technique. The sample of this study was 60 fifth-grade students from a public elementary school. The instrument in this research was a questionnaire developed by students at the Wesleyan University Graduate School, namely the Class 7 Students' Psychosocial Adjustment Needs Questionnaire, with data analysis techniques using the t-test. Findings/Results: Psychosocial learning models that are deliberately structured progressively through traditional games can influence psychosocial development, as well as psychosocial learning models that are deliberately structured can influence psychosocial development. Conclusion: There is a significant difference between the deliberately structured psychosocial learning model and the progressive version in terms of elementary students’ psychosocial development. The progressive model gives continuous stimulation and better support for psychosocial formation because it builds on what has already been learnt. Teachers are encouraged to use more collaborative, contextual approaches to enhance students' social-emotional engagement. Future research should explore different regions or cultures and incorporate mixed methods for a deeper understanding of student experiences